The Association between Vitamin D Intake and Gestational Diabetes Mellitus: A Systematic Review - Artemisia Kokkinari; Maria Dagla; Aikaterini Lykeridou; Georgios Iatrakis (Clinical and Experimental Obstetrics & Gynecology)
Background: Several studies have focused on the role of vitamin D in preventing gestational diabetes mellitus (GDM) but also in improving or preventing the unwanted perinatal outcomes of GDM. Even today, efforts to clarify the relationship between vitamin D deficiency (VDD) in pregnancy and GDM continue. Methods: We conducted research to search for systematic reviews (SRs) of randomized controlled trials (RCTs), in databases at PubMed, Google Scholar, Web of Science, Science Direct, Embase, Cochrane, Crossref and CAS, published from 2016 to 2021. These concerned maternal vitamin D status or taking vitamin D supplements, alone or in combination with other vitamins or minerals in pregnancy and their association with GDM. We used the AMSTAR (assessment of multiple systematic reviews) scoring scale quality and scoring checklist, which assessed the quality of each SR, at low medium or high. Results: Seven SRs of RCTS involving 7902 participants were selected. The results suggest that if pregnant women with GDM take vitamin D supplements, they improve blood vitamin D levels, as well as biomarkers related to blood glucose. It was also shown that pregnant women with GDM who took vitamin D supplements (1000–4762 IU/day) improved the primary GDM outcome measurements such as fasting blood glucose (FBG), glycosylated hemoglobin (HbA1c), serum insulin and homeostasis model of assessment of insulin resistance (HOMA-IR). In addition, improvements were observed in their lipid profile markers, such as total cholesterol (TC), low-dense lipoprotein (LDL), high-dense lipoprotein levels (HDL) and high-sensitivity C-reactive protein (hs-CRP). Also, the adverse outcomes of GDM in both the mother and the newborn appear to have decreased. However, there are studies that do not support the therapeutic effect of vitamin D intake by pregnant women with GDM. Conclusions: In conclusion, taking vitamin D, during pregnancy, for the prevention or treatment of GDM, is controversial and the real benefit unclear. Further RCTs are necessary.